Peran Guru TK Aisyiyah 1 Bukittinggi Sebagai Guru Profesional di masa Pandemi Covid-19 - Andrea Reza; Delfi Eliza (Universitas Lancang Kuning, 2021)
The government has issued a circular on learning policies to prevent the spread of COVID-19. This learning policy demands the role of the teacher as a professional educator. This article aims to describe the role of teachers in learning during the COVID-19 pandemic. The article uses a qualitative descriptive method. This study describes solving problems that occur in the field with data. This research is infinitive data and information from learning activities during the Covid-19 pandemic in PAUD institutions. The research subject is the integrated PAUD Aisyiyah 1 Bukittinggi which has 3 service programs, especially the kindergarten service program. So it is only natural for teachers to act professionally in carrying out the learning process even during a pandemic. That has been done by the TK Aisyiyah 1 Bukittinggi teacher assembly team in early childhood learning activities. As a recommendation for the future, good communication, cooperation, coordination between all parties is needed. Teachers should not only give activities to children without careful calculation. Teachers must appreciate the achievements of students for the efforts they have made while studying from home.